Penyebaran Informasi wisata kuliner pada Instagram @Bogoreatery di Kota Bogor - Natasya Cathelea Millenitri Januatisa; Yunus Winoto; Ute Lies Siti Khadijah (Jurnal Informatio, 2022)
The @Bogoreatry Instagram account utilizes social media to disseminate information in the culinary field, which already has many followers. Information distribution on Instagram social media has its targets and methods that need to be studied to present information effectively. This study aimed to discover how the Instagram account @Bogoreatry disseminated culinary information at the sharing, optimization, management, and engagement stages. In this case, the researcher would make the @Bogoreatry Instagram account the research object. The research method used case studies with a qualitative approach. Based on the study results, the @Bogoreatry account created the sharing stage by creating informative content. The optimize stage was carried out by analyzing the time of information dissemination, the managed stage was by creating teams that have their respective duties, and the engage stage was performed by collaborating with other accounts. The analysis result showed that the users of the @Bogoreatry Instagram account got information and benefited from the @Bogoreatry account. Then the account also managed very well information on culinary tourism in Bogor city. The presence of the Instagram account @Bogoreatry can positively impact various parties, namely between culinary business owners who are assisted in carrying out promotions and likewise with information seekers or tourists visiting Bogor city.